The Christ of the Indian Road - Jones, E. Stanley (Eli Stanley) (New York; Cincinnati The Abingdon Press, 1925)
For those searching for truth and a map to help lead them down the path of The Way.
Keywords: Missions -- India. RELIGION / Christian Ministry / Missions Missions